2022
DOI: 10.36348/sjodr.2022.v07i01.001
|View full text |Cite
|
Sign up to set email alerts
|

“Reconstruction and Rehabilitation of Maxillary Defects Secondary to Mucormycosis”

Abstract: Maxillary defects can occur due to certain bacterial, fungal and viral infections. But in recent time mucormycosis has become prevalent secondary to covid-19 infection. Mucormycosis is an opportunistic fungal infection, which primarily affects diabetic and immunocompromised patients. Surgical excision and debridement of the affected areas can result in significant defects. Reconstruction and rehabilitation of these defects remains a significant challenge for the clinicians because 3-D anatomy of the maxilla se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…While the real reason for such a sharp rise during the second wave is still unknown, it has been discovered that patients with risk diseases as diabetics and immunocompromised who have recovered from COVID-19 infection are more susceptible to mucormycosis. (12 ) In Egypt several studies reported the presence of CAM cases during the third pandemic wave. Fouad et al (20) reported that 96.2% of CAM cases where diabetic patients and 76.9% where patients had previous corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the real reason for such a sharp rise during the second wave is still unknown, it has been discovered that patients with risk diseases as diabetics and immunocompromised who have recovered from COVID-19 infection are more susceptible to mucormycosis. (12 ) In Egypt several studies reported the presence of CAM cases during the third pandemic wave. Fouad et al (20) reported that 96.2% of CAM cases where diabetic patients and 76.9% where patients had previous corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis most frequently occurs in patients with hematological disorders especially malignancies, diabetes mellitus or patients treated with steroids. (9)(10)(11)(12) It might be transmitted through unsterilized oxygen lines and ventilators or even hospital bed linen (13). The inhaled spores can form hyphae that attack the paranasal sinuses and spread further through anatomical sites and blood circulation within the skull triggering rhino-orbital or rhino-cerebral infection (14) A resurrection of the fungal infection has been documented during the pandemic, either in parallel or after the recovery from the viral infection, mitigating what's known as: COVID-associated mucormycosis (CAM).…”
Section: Introductionmentioning
confidence: 99%
“…This seriously impairs the patient's ability to chew, swallow and various functions of stomatognathic system. Therefore, to protect and obturate the palatal deformities following resection, prosthodontic rehabilitation is necessary to improves the psychological aspect of the patient 4 …”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that in people with COVID-19, Mucorales spores germinate more easily due to high glucose, high iron levels, hypoxia, metabolic acidosis, and decreased phagocytic activity of white blood cells due to immunosuppression. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%